6-Phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 and 4: A pair of valves for fine-tuning of glucose metabolism in human cancer - Yi, Mei (Mol Metab, 2018)
BACKGROUND: Cancer cells favor the use of less efficient glycolysis rather than mitochondrial oxidative phosphorylation to metabolize glucose, even in oxygen-rich conditions, a distinct metabolic alteration named the Warburg effect or aerobic glycolysis. In adult cells, bifunctional 6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase (PFKFB) family members are responsible for controlling the steady-state cytoplasmic levels of fructose-2,6-bisphosphate, which allosterically activates 6-phosphofructo-1-kinase, the key enzyme catalyzing the rate-limiting reaction of glycolysis. PFKFB3 and PFKFB4 are the two main isoenzymes overexpressed in various human cancers. SCOPE OF REVIEW: In this review, we summarize recent findings on the glycolytic and extraglycolytic roles of PFKFB3 and PFKFB4 in cancer progression and discuss potential therapies for targeting of PFKFB3 and PFKFB4. MAJOR CONCLUSIONS: PFKFB3 has the highest kinase activity to shunt glucose toward glycolysis, whereas PFKFB4 has more FBPase-2 activity, redirecting glucose toward the pentose phosphate pathway, providing reducing power for lipid biosynthesis and scavenging reactive oxygen species. Co-expression of PFKFB3 and PFKFB4 provides sufficient glucose metabolism to satisfy the bioenergetics demand and redox homeostasis requirements of cancer cells. Various reversible post-translational modifications of PFKFB3 enable cancer cells to flexibly adapt glucose metabolism in response to diverse stress conditions. In addition to playing important roles in tumor cell glucose metabolism, PFKFB3 and PFKFB4 are widely involved in multiple biological processes, such as cell cycle regulation, autophagy, and transcriptional regulation in a non-glycolysis-dependent manner.